PERCEIVED PRICE MENENTUKAN NIAT UNTUK MEREKOMENDASIKAN KEPADA ORANG LAIN DAN NIAT UNTUK BERKUNJUNG KEMBALI PADA WISATA BAHARI DI PROVINSI LAMPUNG - Nurul Husna (TECHNOBIZ : International Journal of Business, 2021)
Since the COVID-19 pandemic, the income of the tourism sector in Indonesia has decreased drastically. The purpose of this study was to determine the effect of perceived price on the intention to recommend to others and the intention to revisit marine tourism in Lampung Province. The sample in this study were 100 visitors to Pahawang Island in Lampung Province. This research uses data analysis method using smartPLS software. The results of this study indicate that perceived price has a significant effect on the intention to recommend to others and the intention to revisit marine tourism in Lampung Province.Keywords: Perceived Price, Intention to Recommend to Others, Intention to Revisit